Safety and tolerability of pioglitazone, metformin, and gliclazide in the treatment of type 2 diabetes. - Belcher, G; Lambert, C; Edwards, G; Urquhart, R; Matthews, DR (2005)
This analysis compares the safety and tolerability of pioglitazone (a thiazolidinedione), metformin (a biguanide), and gliclazide (a sulfonylurea). Data collected from four 1-year, double-blind studies comparing treatment of over 3700 patients with type 2 diabetes with pioglitazone, metformin, or gliclazide have been combined to provide comparative tolerability and safety profiles. All treatments were well tolerated with approximately 6% of patients withdrawing from treatment because of side-effects. The side-effects profile varied between treatments, with pioglitazone being associated with edema, metformin with gastrointestinal side-effects, and gliclazide with hypoglycemia. Cardiovascular outcome was similar with all treatments, with no excess reports of cardiac failure with pioglitazone treatment. Both pioglitazone and gliclazide resulted in mean weight gain, whilst with metformin there was mean weight loss. Mean liver enzyme values decreased with pioglitazone and to a lesser extent with metformin. With gliclazide, mean liver enzyme values increased. The expected small decreases in mean hemoglobin and hematocrit seen with pioglitazone also occurred with metformin and to a lesser degree with gliclazide. The results show that all three drugs are safe, but that tolerability profiles vary. Each treatment provides an alternative therapy for type 2 diabetes, dependent on the particular needs of individual patients.